Final answer:
After simplifying the equation 3x + 3y = -x + 5y to y = 2x, we checked each option and found that A. (1,2) and B. (2,4) are the correct solutions.
Step-by-step explanation:
To find the correct solutions for the equation 3x + 3y = -x + 5y, we need to first simplify the equation by combining like terms. We move all terms involving x to one side and all terms involving y to the other side.
Adding x to both sides gives us 4x + 3y = 5y, and then subtracting 3y from both sides gives us 4x = 2y. This can be further simplified to y = 2x.
Now, we can check each option:
- A. (1,2) - Substituting into y = 2x gives 2 = 2(1), which is true, so this is a solution.
- B. (2,4) - Substituting into y = 2x gives 4 = 2(2), which is true, so this is also a solution.
- C. (4,6) - Substituting into y = 2x gives 6 = 2(4), which is not true (since 8 ≠6), so this is not a solution.
Therefore, the correct solutions are A. (1,2) and B. (2,4).